2016
DOI: 10.1007/s11121-016-0660-5
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Drinking Motives and Friends in Predicting Young Adults’ Alcohol Use

Abstract: While drinking motives are well-established proximal predictors of alcohol use, less is known about their role in event-level drinking behavior. The present study examines whether the interaction between individuals’ drinking motives and the number of friends present at a given moment can predict alcohol consumption over the course of the evening. Using the Internet-based cell phone-optimized assessment technique (ICAT), 183 young adults (53.0 % female, mean age =23.1) in French-speaking Switzerland completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…For example, heavy drinking may have been linked more strongly to social or enhancement motives rather than coping motives , while marijuana use may have been used to manage ongoing, unresolved stressors. Indeed, drinking is both legal and normative among some college students and thus social factors, such as the presence of drinking peers , may have exerted a greater influence on heavy drinking compared to marijuana use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, heavy drinking may have been linked more strongly to social or enhancement motives rather than coping motives , while marijuana use may have been used to manage ongoing, unresolved stressors. Indeed, drinking is both legal and normative among some college students and thus social factors, such as the presence of drinking peers , may have exerted a greater influence on heavy drinking compared to marijuana use.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research is needed to understand more clearly the role of peer context (e.g. quality of peer relationships, peer substance use) in the relations examined here, given a robust body of evidence linking peer‐related factors to substance use among college students . Moreover, we examined the use of emotion regulation strategies to manage stress in particular; however, these strategies may be employed at other times (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Hicks et al (2015), for example, argue that despite the link between trait impulsivity and attentional bias among binge drinkers, it still remains to be demonstrated whether impulsive binge drinkers actually have difficulty controlling their impulses after exposure to alcohol cues in a given situation. Other authors found that drinking motives, which are closely related to personality factors as described above, were only weakly related to the amounts consumed in a given situation, and argue that the effects of drinking motives and possibly also those of other individual-specific factors may be 'overruled' by situational characteristics (Grant et al, 2009;Kuntsche & Kuendig, 2012;Thrul & Kuntsche, 2016). However, even if there is no or little impact, individual characteristics or traits may still interact with situational factors.…”
Section: Correlates and Determinantsmentioning
confidence: 94%
“…However, even if there is no or little impact, individual characteristics or traits may still interact with situational factors. For example, pre-drinking (Kuntsche & Labhart, 2013a), the number of friends present at a drinking occasion (Thrul & Kuntsche, 2016) or the daily mood (Grant et al, 2009) have been found to moderate the impact of drinking motives on the volume of alcohol consumed on a given day.…”
Section: Correlates and Determinantsmentioning
confidence: 99%
“…Data of missing assessments ( n = 818) were imputed by means of chained equations using the Stata ICE procedure . More information about this study design and sample is provided elsewhere . As the question assessing the number of friends present was not included in the next day's questionnaire at 11 a.m., 623 observations (8.0%) were excluded.…”
Section: Methodsmentioning
confidence: 99%